Art in Life and Life in Art. Review of: Razakov, V. Kh. (2017). Kul’tura. Iskusstvo. Zhizn’: Tvorcheskaia monografiia: Nauchno-khudozhestvennye i khudozhestvenno-kriticheskie esse. Tvorcheskie portrety. Ocherki. Razmyshleniia. Aforizmy [Culture. Art. Life: Creative Monograph: Scholarly and Artistic, and Artistic and Critical Essays. Creative Portraits. Essays. Reflections. Aphorisms]. Volgograd: PrintTerra-Design. 260 p. - Pluzhnikova, Natalia N. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
This paper provides a critical survey of the creative monograph Culture. Art. Life published by PrintTherra-Design, a Volgograd publishing house in 2017. The book under review presents a critical approach to the current issues of contemporary art culture in the field of the theatre, cinema, and architecture. The reviewer maintains that the analysis of artistic culture is based on broad factual material, and innovative use of artistic and critical essays, and sketches. The reviewer points out that the analysis of art issues is impossible without reference to the person’s existential experience, and to various forms of everyday life.